AWARENESS AND ATTITUDE OF ISLAMIYYAH SCHOOLS OF INCLUSIVE EDUCATION IN SOUTH WEST, NIGERIA - Yahya, Isiaq Oluwatosin; Olaniyan-Shobowale, Khadijah Olushola; Owoyale-Abdulganiy, Ibrahim Solahudeen; Abdul-Rafiu, Jamiu,; Sanni, Hajarah Monisola (Universitas Labuhanbatu, 2023)
This study assessed the Awareness and Attitude of Islamiyyah Schools on Inclusive Education in South West, Nigeria. This study adopted descriptive research design. The population consists of all the teachers and school leaders available in all Islamiyyah Schools in South west, Nigeria out of which five Islamiyyah Schools (30 across all states), 25 respondents (150 across all states) were selected as using disproportionate random sampling technique. The instruments used for collection of data is a self-constructed questionnaire titled